DEVELOPMENT OF ELECTRONIC FLIGHT BAG (EFB) APPLICATION FOR SMALL TURBOPROP AIRCRAFT WEIGHT AND BALANCE CALCULATION - Maulana Malik, Rahadian
This research aims to develop the application of WAB calculation for X-123 on Electronic Flight Bag (EFB), a small turboprop aircraft, according to Indonesian regulations and to examine the weight and balance characteristics of X-123. Staff Instruction 8900 - 3.3 is analyzed to identify the factors that should be considered in EFB development. The aircraft data such as weight limitations and balance arms are collected from the aircraft flight manual of X-123. The global architecture design and substantial features are, then, proposed as an initial EFB development according to regulations. In the global architecture design, the utilization of a gateway becomes important as a connection between the EFB developer and the client, providing aircraft data changes flexibility to the client. Moreover, the calculation formula is completely discussed in the calculation modules as a substantial feature. A simple calculation model is established to implement the formula in a programming language, Python. Several simulations are undertaken to check the formula and to analyze the weight and balance characteristics of X-123. According to simulation results, the X-123 is a tail-heavy aircraft. Moreover, the payload weight and payload distribution changes can affect significantly the CG location. It is recommended to weigh and assign the payload before flight to ensure flight operation safety. In addition, the proposal of the architecture design and substantial features can be used as a reference and further developed by the Indonesian aviation companies. Whilst, the simulation analysis can be used as a guide for X-123 operators in developing aircraft loading procedures.